Standards for nursing agencies in South Africa - Marie Muller (AOSIS, 2001)
The purpose with this research is to formulate standards for nursing agencies in South Africa. Opsomming Die doel met hierdie navorsing is om standaarde vir verpleegagentskappe in Suid-Afrika te formuleer *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.